2021
DOI: 10.3390/jcm10102058
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of C-Reactive Protein to Albumin Is an Independent Predictor of Malignant Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: There is growing evidence to indicate that inflammatory reactions are involved in cancer progression. The aim of this study is to assess the significance of systemic inflammatory biomarkers, such as the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), the ratio of C-reactive protein to albumin ratio (CAR), the prognostic nutritional index (PNI) and the modified Glasgow prognostic score (mGps) in the diagnosis and prognosis of malignant intraductal papillary mucinous neoplasms (IPMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The role of the ratio between the CAR has been less investigated. Very recently, Serafini et al conducted a retrospective analysis on 83 patients who underwent pancreatic resection for IPMNs [ 50 ]. Their results suggest that CAR > 0.083 was a statistically significant predictor of invasive carcinoma or high-grade dysplasia in IPMNs with a sensitivity of 52% and a specificity of 93%.…”
Section: Circulating Humoral Predictors Of Malignancymentioning
confidence: 99%
“…The role of the ratio between the CAR has been less investigated. Very recently, Serafini et al conducted a retrospective analysis on 83 patients who underwent pancreatic resection for IPMNs [ 50 ]. Their results suggest that CAR > 0.083 was a statistically significant predictor of invasive carcinoma or high-grade dysplasia in IPMNs with a sensitivity of 52% and a specificity of 93%.…”
Section: Circulating Humoral Predictors Of Malignancymentioning
confidence: 99%
“…Recently, the C-reactive protein-to-albumin ratio (CAR) was identified as a non-specific marker of systemic inflammation (14)(15)(16). CAR has been shown to have some clinical impact on both the short-and long-term oncological outcomes of patients with gastrointestinal cancer, including hepatocellular, esophageal, colorectal, and pancreatic, and some studies have shown similar tendencies for gastric cancer.…”
mentioning
confidence: 99%
“…This Special Issue of the Journal of Clinical Medicine , entitled “Recent Advances in Pancreatic Neoplasms”, focuses on new possible strategies to treat pancreatic neoplasms, especially pancreatic adenocarcinoma (PDCA). This Special Issue contains 13 articles, 11 studies and 2 review articles, focusing on the pancreatic ductal adenocarcinoma ( n = 10), intraductal papillary mucinous neoplasm (IPMN) ( n = 1), neuroendocrine tumors ( n = 1) and secondary tumor to the pancreas ( n = 1) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Seven papers [ 4 , 5 , 6 , 9 , 10 , 11 , 14 ] explored new prognostic factors potentially able to stratify patients with pancreatic cancer and different survival rates in order to select the adequate treatment.…”
mentioning
confidence: 99%
“…This Special Issue contains 13 articles, 11 studies and 2 review articles, focusing on the pancreatic ductal adenocarcinoma ( n = 10), intraductal papillary mucinous neoplasm (IPMN) ( n = 1), neuroendocrine tumors ( n = 1) and secondary tumor to the pancreas ( n = 1) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Seven papers [ 4 , 5 , 6 , 9 , 10 , 11 , 14 ] explored new prognostic factors potentially able to stratify patients with pancreatic cancer and different survival rates in order to select the adequate treatment. Allen et al [ 6 ] examined the relationship between the daily rate of change in CA 19-9 over the first 90 days of chemotherapy for unresectable and metastatic pancreatic cancer and the pretreatment levels of neutrophils, lymphocytes and platelets with an overall progression-free survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation